Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Quantum-like nonseparable structures in optical beams - Aiello, Andrea; Töppel, Falk; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2015)
When two or more degrees of freedom become coupled in a physical system, a number of observables of the latter cannot be represented by mathematical expressions separable with respect to the different degrees of freedom. In recent years it appeared clear that these expressions may display the same mathematical structures exhibited by multiparty entangled states in quantum mechanics. In this work, we investigate the occurrence of such structures in optical beams, a phenomenon that is often referred to as 'classical entanglement'. We present a unified theory for different kinds of light beams exhibiting classical entanglement and we indicate several possible extensions of the concept. Our results clarify and shed new light upon the physics underlying this intriguing aspect of classical optics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: classical entanglement; non-separability; optical beams